Implementation of coaching and mentoring methods in teaching Kazakh literature to the secondary school students - Karinov, Abylay; Smagulov, Zhandos; Takirov, Sarzhan; Zhumagulov, Aitbay (Frontiers in Education, 2023)
This paper explores the use of coaching and mentoring methods in teaching literature to secondary school students. This innovative pedagogical approach has not been previously practiced in Kazakhstani schools. The study employs a one-month coaching and mentoring initiative tailored for secondary school students. This qualitative study employed the collection of the reflective journal "life scenario" and the focus group interview with participants. The data obtained from the reflective journal and focus group interview were subjected to content analysis. The integration of coaching and mentoring methods into literature pedagogy is postulated as a catalyst for inspiring students to develop "life scenarios," thereby propelling them towards goal achievement and academic success. Additionally, the paper suggests integrating more practical exercises from business, psychology, coaching, and mentoring in literature lessons at the secondary school level.